Răspunsuri

2014-05-11T17:20:56+03:00
(-9)-(-2)=(-9)+(+2)=-7
-25-(+8)=-25+(-8)=3-3
 +15-(-9)=+25+(+9)=+34
 +11-(-5)=+11+(+5)=+15
 -21-(+17)=-21+(-17)=-38
 0-(-16)=
 +11-(-8)=+11+(+8)=+18
 +12-(+13)=+12+(-23)=-15
 0-(+9)=nu se poate
 -6-(-4)=-6+(+4)=+10
 -4-(+10)=-4+(-10)=-14
 +9-(-9)=0
 +11-(-12)=+11+(+12)=+23
 -2-(+13)=-2+(-13)=-11
 0-(-19)=
 -7-(-8)=
-7+(+8)=+1

2 3 2
Cel mai inteligent răspuns!
2014-05-11T17:44:39+03:00
(-9)-(-2)=(-9)+(+2)=-7
-25-(+8)=-25+(-8)=3-3
 +15-(-9)=+25+(+9)=+34
 +11-(-5)=+11+(+5)=+15
 -21-(+17)=-21+(-17)=-38
 0-(-16)=
 +11-(-8)=+11+(+8)=+18
 +12-(+13)=+12+(-23)=-15
 0-(+9)=nu se poate
 -6-(-4)=-6+(+4)=+10
 -4-(+10)=-4+(-10)=-14
 +9-(-9)=0
 +11-(-12)=+11+(+12)=+23
 -2-(+13)=-2+(-13)=-11
 0-(-19)=
 -7-(-8)=
-7+(+8)=+1
2 5 2